Hot Electron‐Based Solid State TiO2|Ag Solar Cells. Issue 7 (21st January 2016) - Barad, Hannah‐Noa; Ginsburg, Adam; Cohen, Hagai; Rietwyk, Kevin J.; Keller, David A.; Tirosh, Shay; Bouhadana, Yaniv; Anderson, Assaf Y.; Zaban, Arie
Abstract : The present work reports a simple and direct sputtering deposition to form solid state TiO2 |Ag independent plasmonic solar cells. The independent plasmonic solar cells are based on a Schottky barrier between two materials, TiO2 and Ag. The Ag functions as the absorber generating "hot" electrons, as well as the contact for the solar cell. The Ag sputtering is performed for different durations, to form Ag nanoparticles with a wide size distribution on the surface of rough spray pyrolysis deposited TiO2 . Incident photon to current efficiency (IPCE) measurements show photovoltaic activity below the TiO2 bandgap, which is caused by the silver nanoparticles that have a wide plasmonic band, leading to the generation of "hot" electrons. X‐ray photoelectron spectroscopy analysis supports the "hot" electron injection mechanism by following the Ag plasmon band and detecting local photovoltages. The measurements show that electrons are formed in the Ag upon illumination and are injected into the TiO2, producing photovoltaic activity. J – V measurements show photocurrents up to 1.18 mA cm −2 and photovoltages up to 430 mV are achieved, with overall efficiencies of 0.2%. This is, to our knowledge, the highest performance reported for such independent plasmonic solar cells. Abstract : TiO2 |Ag solid state plasmonic solar cells are shown to give efficiencies of 0.2%, which is high for these types of cells. The Ag is sputtered directly on to the TiO2, which has a rough surface, enabling formation of Ag nanoparticles. Quantum efficiency measurements and electrical analysis reveal that the "hot" electron mechanism is responsible for the photovoltaic activity.